2007
DOI: 10.1111/j.1460-2695.2006.01055.x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of strength properties of thin polycrystalline silicon films for MEMS applications

Abstract: The aim of this work is to characterize the strength properties of polycrystalline silicon (polysilicon) with the use of tensile and bending test specimens. The strength of thin polysilicon films with different geometry, size and stress concentrations has been measured and correlated with the effective size of the specimen and its stress distribution. The test results are evaluated using a probabilistic strength approach based on the weakest link theory with the use of STAU software. The use of statistic metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 12 publications
(16 reference statements)
0
17
0
Order By: Relevance
“…The increased r f and increased variability at notch features has been demonstrated and analyzed in several prior studies, e.g., Refs. 84,131,and 236. Chasiotis and Knauss evaluated the effect of twodimensional circular and elliptical perforations in the center of a polysilicon tensile bar with radii of curvature ranging from 1 to 8 lm and nominal stress concentration factors of 3-8. 134 They showed that after accounting for the SIF, samples with a 1 lm radius perforation were still 50% stronger than samples with an 8 lm radius.…”
Section: Geometrymentioning
confidence: 99%
“…The increased r f and increased variability at notch features has been demonstrated and analyzed in several prior studies, e.g., Refs. 84,131,and 236. Chasiotis and Knauss evaluated the effect of twodimensional circular and elliptical perforations in the center of a polysilicon tensile bar with radii of curvature ranging from 1 to 8 lm and nominal stress concentration factors of 3-8. 134 They showed that after accounting for the SIF, samples with a 1 lm radius perforation were still 50% stronger than samples with an 8 lm radius.…”
Section: Geometrymentioning
confidence: 99%
“…18 ranks the resulting scatter in life data on a two-parameter Weibull probability plot. Weibull approaches are commonly used [30] to estimate the probability of survival of a mechanical system. The slope of the two-parameter Weibull fit provides a measure of scatter in the data.…”
Section: Effect Of Microstructure Topologymentioning
confidence: 99%
“…Here we a-priori assume that in case of impacts a major role is played by the propagation of cracks at grain boundaries and within grains [4]. Since polysilicon is brittle at room temperature [5], a local rupture can occur when the stress field satisfies a stress-based failure criterion. We therefore avoid running micro-scale simulations; instead, an experimentally determined tensile strength of the polysilicon is required.…”
Section: Introductionmentioning
confidence: 99%